Ecological validity of session RPE method for quantifying internal training load in tennis - Gomes, R. V.; Moreira, A.; Lodo, L.; Capitani, C. D.; Aoki, M. S.; Foster, C.; Jenkins, D. (International Journal of Sports Science and Coaching, 2015)
This study aimed to verify the ecological validity of the session rating of perceived exertion (session RPE) method for quantifying internal training load (ITL) in competitive tennis players. Twelve professional tennis players (18.5 ± 0.4 years; 178.0 ± 4.0 cm; 72.4 ± 6.0 kg) participated in this study. In total, 384 on-court tennis training sessions, 23 simulated matches and 13 official matches were monitored. ITL was then calculated for each session using session RPE and HR-based methods. All individual correlations between the session RPE method and the HR-based method were significant (r = 0.58 - 0.89: p < 0.01). The correlation coefficients between methods during on court tennis training sessions, simulated and official matches were r = 0.74, r = 0.57 and r = 0.99, respectively. The results support the validity of session RPE as a practical method for quantifying ITL in professional tennis players. ABSTRACT FROM AUTHOR